2020
DOI: 10.1155/2020/1692930
|View full text |Cite
|
Sign up to set email alerts
|

“Effects of Tobacco Smoke on Aeroallergen Sensitization and Clinical Severity among University Students and Staff with Allergic Rhinitis”

Abstract: Allergic diseases, affecting a variety of organs, have continuously increased both in developed and developing countries. Tobacco smoke exposure increases prevalence of allergic rhinitis (AR) and may affect allergic sensitization. This study was designed to compare indoor-aeroallergen sensitization between those not exposed and exposed to tobacco smoke in university students and staff with allergic rhinitis. A cross-sectional descriptive study among university students and staff with allergic rhinitis was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…They have two times more chances in mortality as compared with those who are nonsmoker. 18 Quitting cigarette smoke as a first and secondhand smoker improved health benefits whereas some or all the reduced life expectancy can be improved depending on the age a person quits. 14 Recent research by Kasote et al, showed the antioxidant property of some plants used as therapeutic entities.…”
Section: Discussionmentioning
confidence: 99%
“…They have two times more chances in mortality as compared with those who are nonsmoker. 18 Quitting cigarette smoke as a first and secondhand smoker improved health benefits whereas some or all the reduced life expectancy can be improved depending on the age a person quits. 14 Recent research by Kasote et al, showed the antioxidant property of some plants used as therapeutic entities.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis found that children actively smoking had an increased risk of AR, while those exposed to second-hand smoke (passive smoking) had a much larger increased risk for AR [6]. In a French epidemiological study, children actively smoking were almost three times more likely to experience symptoms of AR than non-smoking children [19]. Maternal smoking was also found to contribute to AR development in the child.…”
Section: Tobacco Smokementioning
confidence: 97%
“…Indoor air pollution including tobacco smoke, indoor allergens (e.g., dust mites, pet dander, molds), and other pollutants (e.g., cleaning chemicals) all contribute to the development of AR and the aggravation of symptoms [9]. Individuals in western countries spend the vast majority of their time indoors, and more than 90% of the population live in places where air quality does not meet World Health Organization (WHO) standards, leading to increased rates of AR in children [19]. Furthermore, during the Health Effects of School Environment (HESE) project, it was found that 78% of children attending schools in Norway, Sweden, Denmark, France, and Italy are exposed to high levels of inhalable particulate matter with a diameter of 10 micrograms (PM 10 ), and 66% are exposed to carbon dioxide (CO 2 ) over 1000 ppm [20].…”
Section: Indoor Exposuresmentioning
confidence: 99%
See 2 more Smart Citations